2017
DOI: 10.1177/0954406217718571
|View full text |Cite
|
Sign up to set email alerts
|

Disbond detection in a composite honeycomb structure of an aircraft vertical stabilizer by fiber Bragg gratings detecting guided ultrasound waves

Abstract: Efficient and accurate nondestructive inspection systems that save time can benefit scheduled maintenance of aircraft structures. Portable nondestructive inspection techniques capable of scanning larger area structures could find great utility and save considerable time and labor. Contemporary fixed location nondestructive inspection systems, such as the gold standard water-coupled ultrasound imaging by the “squirter” require structural disassembly of the part to be inspected and transportation to/from dedicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…When acting as a strain sensor, the fiber is stretched or compressed, which causes a change in the period of the microstructure and in the Bragg wavelength. Fiber Bragg gratings have been used with LW‐based NDT techniques, 57,58 but their application to adhesive joints has been limited 59 …”
Section: Adhesive Jointsmentioning
confidence: 99%
“…When acting as a strain sensor, the fiber is stretched or compressed, which causes a change in the period of the microstructure and in the Bragg wavelength. Fiber Bragg gratings have been used with LW‐based NDT techniques, 57,58 but their application to adhesive joints has been limited 59 …”
Section: Adhesive Jointsmentioning
confidence: 99%
“…It has been demonstrated that gravity has noticeable effects on the precision of positioning systems, inertial navigators, and guided systems as well as the mechanical performance of thin structural elements applicated in aerospace vehicles [4][5][6]. Typically, such thin structural elements include large-scale covering shells/plates of aerospace protection structures, vertical stabilizers of accelerated aircraft or missiles, and structural components of specific systems strongly influenced by varying gravity [7,8]. These structures, relatively thin, are subjected to hyper gravity as the flight vehicle accelerates.…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, honeycomb materials have been employed in automotive, 24 railway, 57 ship 8–10 and aerospace structures. 1113…”
Section: Introductionmentioning
confidence: 99%